STEAM TECHNOLOGIES IN THE ORGANIZATION OF PRESCHOOL EDUCATION - Rajabov Feruz Baxrom o’g’li (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation:  This  article  talks  about  the  STEAM  technology,  its  role  in  the education system and its impact on the children’s thinking ability, the development of the STEAM education system in Uzbekistan, and the actions and decisions that have taken place.